Effect of water current on underwater glider velocity and range - Javaid, M.Y. (Penerbit UTM Press, 2016)
An autonomous underwater glider speed and range is influenced by water currents. This is compounded by a weak actuation system for controlling its movement. In this work, the effects of water currents on the speed and range of an underwater glider at steady state glide conditions are investigated. Extensive numerical simulations have been performed to determine the speed and range of a glider with and without water current at different net buoyancies. The results show that the effect of water current on the glider speed and range depends on the current relative motion and direction. In the presence of water current, for a given glide angle, glide speed can be increased by increasing the net buoyancy of the glider. Â© 2016 Penerbit UTM Press. All rights reserved.